PERAN ISTRI SEBAGAI PEKERJA BAKAL PECI DALAM MEMBANGUN KETAHANAN KELUARGA DI DESA WARUK KECAMATAN KARANGBINANGUN KABUPATEN LAMONGAN - Zahroh, Fitrotuz; Jatiningsih, Oksiana (Kajian Moral dan Kewarganegaraan, 2023)
AbstractFamily resilience involving the role of the wife is influenced by several factors such as the duration of difficult situation to face, the stage of family development, eksternal sources of internal support and commitment. The aim of this research is to describe the role of the wife as a future worker in building family resilience. This research approach is qualitative. The focus of this research is the role of wives as future workers in building family resilience from the aspect of socio-cultural resilience. The location of this research is Waruk Village, Karangbinangun District, Lamongan Regency. The selection of subjects was carried out using a purposive sampling technique based on the criteria of workers who would work outside the home, with working hours > 48 hours per week, as well as a high income contribution, namely the wife's income > 50%, and actively participating in activities in the community and six research subjects were obtained. Data was collected through in-depth interviews. The data analysis technique uses the Miles and Huberman technique through four stages of data collection, data reduction, data presentation and data verification compared to Robert K. Merton's structural functionalism theory. There are seven ways to build family resilience, namely: 1) managing time, 2) self-management, 3) prioritizing, 4) collaborating, 5) establishing good relationships, 6) participating in PKK activities, 7) strengthening understanding of religion. The research results show that equilibrium in the family will be achieved if the roles are carried out well by the role holders. However, in this case there is another factor, namely the values held by the wife who works as a bridesmaid, namely the values of respect and patience, which then become internal encouragement that shapes the behavior and decisions of research subjects who are sincere in carrying out role dualism. This is the key to forming family resilience.